Effects of high-intensity training on performance and physiology of endurance athletes - Paton, C. D.; Hopkins, W. G. (Sportscience, 2005)
Most endurance athletes use high-intensity training to prepare for competitions. In this review we consider the effects of high-intensity interval and resistance training on endurance performance and related physiological measures of competitive endurance athletes. METHODS: There were 22 relevant training studies. We classified training as intervals (supramaximal, maximal, submaximal) and resistance (including explosive, plyometrics, and weights). We converted all effects on performance into percent changes in mean power and included effects on physiological measures that impact endurance performance. FINDINGS: All but one study was performed in non-competitive phases of the athletes` programs, when there was otherwise little or no high-intensity training. Endurance performance of the shortest durations was enhanced most by supramaximal intervals (~4%) and explosive sport-specific resistance training (4-8%). Endurance performance of the longest durations was enhanced most by intervals of maximal and supramaximal intensities (~6%), but resistance training had smaller effects (~2%). Interval training achieved its effects through improvements of maximum oxygen consumption, anaerobic threshold, and economy, whereas resistance training had benefits mainly on economy. Effects of some forms of high-intensity training on performance or physiology were unclear. CONCLUSIONS: Addition of explosive resistance and high-intensity interval training to a generally low-intensity training program will produce substantial gains in performance. More research is needed to clarify the effects of the various forms of high-intensity training on endurance performance, to determine whether prescribing specific forms of resistance training can improve specific deficits of an endurance athlete's physiology, and to determine the effects of combining the various forms in periodized programs.